From Provider to Partner: Reconstructing the Legal Concept of Livelihood Obligation in Indonesian Islamic Family Law through the Lens of Gender Justice and Maqāṣid al-Sharīʿah - Muhammad Danil; Vito Dasrianto; Elva Mahmudi; Asfar Hamidi Siregar (Islamic Family Law Study Program, Sharia Faculty, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The persistence of the husband’s exclusive maintenance obligation in Indonesia’s Compilation of Islamic Law (KHI) no longer reflects the contemporary reality in which a growing number of women serve as primary breadwinners. This study examines the normative inadequacy of the existing legal framework and reconstructs the concept of marital maintenance through the perspectives of gender justice and Maqāṣid al-Sharīʿah. Employing a qualitative library-based approach, the research integrates classical fiqh analysis with Fazlur Rahman’s Double Movement hermeneutics, Faqihuddin Abdul Kodir’s Qirā’ah Mubādalah, and Jasser Auda’s maqāṣid framework. The findings reveal four systemic limitations in the classical doctrine of nafkah: the presumption of unilateral male economic agency, the subordination embedded in the ṭā‘ah–nafkah nexus, the absence of proportional responsibility, and the lack of legal recognition for wives who become primary providers. These limitations create a normative gap that undermines legal certainty, gender justice, and the objectives of Islamic law in contemporary Indonesia. The study proposes a reconstruction model based on mushārakah naẓariyyah (proportional shared responsibility), grounded in the principle of ta‘āwun (mutual cooperation), which redefines financial responsibility according to the spouses’ respective capacities. The principal contribution of this article lies in developing an integrated maqāṣid-based framework that bridges classical Islamic jurisprudence with contemporary socio-economic realities and provides normative guidance for reforming Indonesian Islamic family law toward a more equitable and context-responsive legal system.